A Sustainable Two-Echelon Logistics Model with Shipment Consolidation - Noha A. Mostafa; Omar Eldebaiky (Logistics, 2023)
Background: Shipment consolidation is a concept in logistics management in which two or more shipments are transported by using the same vehicle with the aim of using less resources. Methods: The objective of this manuscript is to study shipment consolidation and assess its impact on cost environment, to achieve this, a mathematical model was developed to optimize shipment consolidation while reducing the emissions and minimizing the costs. Results: A case study from major dairy products manufacturers in Egypt was used to validate the model and evaluate the outcomes. A comparison was made between two transportation models, with and without consolidation. Results show that shipment consolidation reduced the total costs by 40% in addition to consuming less fuel, and consequently producing less emissions. Conclusions: These findings emphasize the importance of shipment consolidation and how it can be used to achieve more sustainability in logistics management.